Application of spectroscopy (1HMRS) to assess liver metabolite concentrations in rats with intrauterine growth restriction. (18th April 2017) - Wang, Tao; Chen, Pingyang; Bian, Dujun; Chen, Juncao
Abstract: Objective : Proton magnetic resonance spectroscopy ( 1 H-MRS) measurement of liver metabolism in intrauterine growth restriction rats has seldom been reported. This study investigated the application of 1 H-MRS in assessing liver metabolism in newborn pups that experienced intrauterine growth restriction. Methods : Intra-uterine growth restriction was established by feeding rats low-protein diets during pregnancy. Newborn pups received conventional magnetic resonance imaging and 1 H-MRS using a 3.0T whole body MR scanner at 3, 8 and 12 weeks post birth. Results : The success rate of 1 H-MRS was 83.33%. Significantly lower body weight, BMI and body length at 3 weeks as well as significantly lower body weight, BMI and waist circumference at 8 and 12 weeks were observed in newborn pups of IUGR rats compared with pups of control rats. Significant differences in ACho/H2 O, ACr/H2 O, AGlx/H2 O and ALipid/H2 O at 3 and 8 weeks as well as significant differences in ACr/H2 O, ALipid/H2 O and AGlx/H2 O at 12 weeks were observed between pups of control rats and pups of IUGR rats. Conclusion : 1 H-MRS allows noninvasive assessment of liver metabolism in the rat and demonstrated the poor liver development of rats that experienced IUGR.